Analysis of The Influence of Wind Speed and Particle Size On Temperature Increase During The Coal Combustion Process of MT-46, BB-50, and Al-55 at PT Bukit Asam Tbk., Tanjung Enim, South Sumatra - Reni Arisanti; Ahmad Husni (Publikasi Indonesia, 2025)
Swabakar is an event where coal can burn on its own. The purpose of the PT Bukit Asam Tbk Laboratory is to analyze the influence of wind speed and grain size differences and determine the value of transition temperature and the normality test of time and temperature data of coal samples. The research method used is to measure wind speed using an anemometer and measure the coal temperature before and after the swab. It can be seen from the results of the discussion that coal with a grain size of 13 mm experiences a faster swab process than coal with a grain size of 50 mm. The results showed that coal with a grain size of 13 mm experienced a faster swab than a size of 50 mm. The order of transition temperature values based on the grain size of 13 mm was MT-46 < BB-50 < AL-55, while at 50 mm the same results were found. This shows that MT-46 coal is more susceptible to swabbing than other types. Normality testing of time and temperature data shows that all data are distributed normally, so the validity of the research results can be accounted for. This study concludes that the smaller the size of the coal grains, the faster the oxidation process leads to spontaneous combustion. Wind speed also plays a role in accelerating the spread of oxygen into the coal pile, which increases the risk of swabbing. The implications of this study are important for the coal mining industry to consider the factors of grain size and wind speed in stockpile management to reduce the risk of waste and maintain the quality of coal.